1991
DOI: 10.1159/000276218
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid Tumor of the Larynx

Abstract: Typical carcinoid neoplasms of the larynx are extremely rare tumors. The total number of known and documented cases is likely no more than 13. The neoplasm mainly affects males at an average age of 58 years and appears grossly as a polypoid or sessile submucosal nodule with an average 1.8 cm in size. Their predominant location is the supraglottis with the arytenoid and the aryepiglottic fold being the most frequent sites. Histologically, they are characterized by organoid architecture, uniform cellular feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Moreover, octreoscan may demonstrate the presence of somatostatin receptors in tumor cells that can be amenable to radiometabolic treatment [4, 14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, octreoscan may demonstrate the presence of somatostatin receptors in tumor cells that can be amenable to radiometabolic treatment [4, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…Well differentiated NETs of head and neck have been classically thought to be indolent; however, recent data have shown that their biologic behavior is significantly worse than other NETs in the body and locoregional metastasis reported rates are around 30% [2, 8, 14]. Woodruff and Senie found that well differentiated, grade 2, NETs of the larynx had an aggressive nature with metastasis to neck nodes in 43% of cases and to distant sites in 44% and five-year survival of 48% [6].…”
Section: Discussionmentioning
confidence: 99%
“…Because chemotherapy is of no value in managing atypical carcinoid tumors, except in cases of metastatic disease, and because the therapeutic effect of radiotherapy is also questionable, surgical resection should be advocated for patients with primary atypical carcinoid tumors, with accompanying elective neck dissection if the cervical lymph nodes are clinically negative at diagnosis. Radical or modified radical neck dissection should be performed in cases of positive cervical lymph nodes 5–7. To the best of our knowledge, only a few reports have described surgical approaches, including partial laryngectomy for limited lesions and total laryngectomy for advanced tumors or as postirradiation salvage management 4, 7.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical carcinoid tumors are aggressive neoplasms with a high risk for widespread metastasis. They seem to be unresponsive to chemotherapy, and the role of radiotherapy alone has been regarded as controversial 4–6. Therefore, wide surgical excision should be the treatment of choice.…”
mentioning
confidence: 99%
“…Histologically, the tumor shows organoid formations of cells that are monotonous, with scanty clear or eosinophilic cytoplasm. The defining characteristics of the typical carcinoid tumor are the absence of pleomorphism, necrosis, or invasion, and only rare mitotic figures [6][7][8][9] (Fig 2).…”
Section: Typical Carcinoidmentioning
confidence: 99%